Representation of Urban Sufism in Constructing Urban Muslim Piety in Digital Media - Diar Mukti Asri; Raysha Ramadhani; Surawan Surawan (AL - IBRAH, 2025)
In recent years, social media has become an important arena for expressing religious identity, including the emergence of digital Sufism among urban Muslims. This study examines how urban Sufism is represented in digital media that blends Sufi values with elements of popular culture, addressing the limited scholarly attention toward its role in shaping contemporary religious identity. This qualitative research employs content analysis and library study, drawing data from YouTube and Instagram. The analysis is guided by Stuart Hall’s theory of representation and Charles Taylor’s theory of identity. The findings show that digital representations of urban Sufism function not only as a medium of da‘wah but also as a dynamic space where pious identity is negotiated and socially validated through online engagement. These representations illustrate how Islamic spirituality adapts to urban lifestyles while interacting with global popular culture. However, the phenomenon also raises concerns such as spiritual simplification, authority fragmentation, and the commodification of religiosity. The study concludes that maintaining authenticity and spiritual depth is crucial for content creators and preachers in utilizing digital platforms for inclusive da‘wah.